ANALISIS MODEL TARIKAN PERGERAKAN DI PASAR DEPOK JAYA - Fricilia, Maya; Wiyono, Eko; Fadhilah, Khoirunnisa Fitria; Abiyyu, Muhammad (Journal of Civil Engineering and Infrastructure Technology, 2024)
The Depok Jaya Market, located in the city of Depok, has a relatively high level of activity. The travel attraction in Depok Jaya Market in this study was conducted through a survey method using questionnaires to determine socio-economic characteristics. From the research results, there is a high level of activity in Depok Jaya Market, a shopping center with a building area of Â± 2,332 m2, capable of attracting 700 visitors per day. The obtained data were processed using SPSS software by conducting correlation tests, and then regression analysis was performed to obtain equation models. From the regression analysis results, a multiple regression model was found consisting of Y1 = 16.667 + 0.006 (X5) with a coefficient of determination (R2) = 0.758, Y2 = 10,000 + 0.003 (X5) with a coefficient of determination (R2) = 0.273. This model explains that the independent variable influencing the magnitude of vehicle travel attraction is the parking area (X5). Then, from the primary data, a multiple regression model was obtained consisting of: Y1 = 0.437 + 0.244 (X5) + 0.155 (X6) + 0.531 (X11), which means Cleanliness (X5), Price (X6), and Length of Visit (X11) collectively influence 40.9% on Last Visit; Y3 = 0.437 + 0.244 (X5) + 0.155 (X6) + 0.531 (X11), which means Cleanliness (X5), Price (X6), and Length of Visit (X11) collectively influence 40.9% on Visit Intensity (Y2); Y4 = 1.225 + 0.581 (X11), meaning that the last visit influences 33% on the data for the length of visit.